Argon plasma coagulation for the treatment of chronic radiation proctitis – real-world data from Indonesian National Cancer Center - Lianda Siregar; Imelda Maria Loho; Agus Sudiro Waspodo; Rahmanandhika Swadari; Benedicta Audrey Maharani (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy, 2021)
Background: This study aimed to evaluate the endoscopic features and clinical outcome of patients with chronic radiation proctitis (CRP) at one year after argon plasma coagulation (APC) treatment.